FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN UNTUK MEMBAYAR PAJAK (Students' Journal of Accounting and Banking, 2012)
This study aims to test the awareness of paying taxes, and knowledge will pemahamana tax laws, a good perception of the effectiveness of the system of taxation, and financial penalties against the willingness to pay taxes. Taxpayer attitudes that tend to assume that taxes are a wasted expenditure, it is also one of the factors that inhibit and reduce the awareness of taxpayers to fulfill tax obligations.The data used are the primary data in the period of 2011.  Researchers used a convenience sampling and obtaining a sample of 99 respondents. The research data were then tested by multiple linear regression using SPSS 16 application program to test the awareness of tax paying, knowledge and understanding of tax laws, a good perception of the effectiveness of the system of taxation, and financial penalties against the willingness to pay taxes.The results showed that the attitude of taxpayers towards consciousness of paying taxes and taxation knowledge and understanding of significant effect on willingness to pay taxes, taxpayer attitudes towards a better perception of the effectiveness of the tax system and financial penalties are not significant effect on willingness to pay taxes.Keywords: willingness to pay taxes, public awareness, knowledge and understanding of tax laws, a good perception of the effectiveness of the tax system, financial penalties.